2018
DOI: 10.1080/00952990.2018.1458234
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in opioid use and medical issues during buprenorphine/naloxone treatment

Abstract: Background: There are sex differences in buprenorphine/naloxone clinical trials for opioid use. Whereas women have fewer opioid-positive urine samples, relative to men, a significant decrease in opioid-positive samples was found during treatment for men, but not women. In order to inform sex-based approaches to improve treatment outcomes, research is needed to determine if opioid use, and predictors of opioid use, differs between men and women during treatment. Objectives: To test for sex differences in opio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…Furthermore, the samples in the reviewed articles may represent a lower than average SES population, which is consistent with the population of individuals with OUDs—a critical factor to consider, because this group experiences a high level of health disparities related to OUDs (King et al, 2014; Singh et al, 2019). These findings are important given that research suggests that females, people of low SES, and racially/ethnically minoritized individuals experience significant health disparities related to opioid use and may not respond as well to pharmacological treatment (Barbosa-Leiker et al, 2018; Crist et al, 2013; Parran et al, 2010; Pro et al, 2020). Moreover, people who are both low SES and from a minoritized racial/ethnic background may experience even greater, additive, or multiplicative risk for harm related to OUD.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Furthermore, the samples in the reviewed articles may represent a lower than average SES population, which is consistent with the population of individuals with OUDs—a critical factor to consider, because this group experiences a high level of health disparities related to OUDs (King et al, 2014; Singh et al, 2019). These findings are important given that research suggests that females, people of low SES, and racially/ethnically minoritized individuals experience significant health disparities related to opioid use and may not respond as well to pharmacological treatment (Barbosa-Leiker et al, 2018; Crist et al, 2013; Parran et al, 2010; Pro et al, 2020). Moreover, people who are both low SES and from a minoritized racial/ethnic background may experience even greater, additive, or multiplicative risk for harm related to OUD.…”
Section: Discussionmentioning
confidence: 97%
“…Of particular concern, none of the reviewed studies reported on the inclusion of gender diverse (e.g., transgender or gender non-binary) individuals. It is further problematic that articles did not differentiate between biological sex and socially constructed gender, as biological sex may differ from expressed gender, but sex can affect efficacy of medications for OUD, making it critical to know whether reported samples are reflecting biological sex or gender identity (Barbosa-Leiker et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical research has revealed numerous sex-dependent differences in terms of patterns of use and response to treatment in opioid addicted patients, with women being more likely to use prescription opioids than men, such as Vicodin ® and Oxycodone [ 187 ], and to benefit from complementary treatment for medical problems during opioid replacement therapy [ 188 ]. Sex-dependent differences have also been observed in pain perception and in the response to opioids for pain relief [ 189 , 190 ].…”
Section: Synthetic Opioidsmentioning
confidence: 99%
“…Patient compliance with naltrexone is notoriously poor even when naltrexone is combined with opiate abstinence incentives (Jarvis et al, 2019;Jarvis et al, 2018;Lee et al, 2018). Furthermore, some patients still relapse on current FDA-approved treatments (Barbosa-Leiker et al, 2018;Tkacz et al, 2012) highlighting the need for preclinical research to develop effective and readily accessible candidate OUD treatments.…”
Section: Introductionmentioning
confidence: 99%